2023
DOI: 10.3390/healthcare11070990
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety and Antidepressants and Anxiolytics Use in Spanish Informal Caregivers according to the Physical Activity Frequency: EHSS 2014–2020

Abstract: Depression and anxiety are two of the most common mental diseases both in formal and nonformal caregivers. Physical activity during leisure time seems to have benefits on their practitioner’s mental health. This study aimed to analyze the associations between physical activity frequency (PAF) and depression and anxiety status, as well as antidepressant and anxiolytic use in Spanish nonformal caregivers. A cross-sectional study with data from the 2014 and 2020 European Health Interview Surveys in Spain (EHSS) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…As mentioned above, these two disorders can affect any person of any age, gender, ethnicity, etc. However, studies have shown that one of the roles with a higher risk of manifesting psychological problems is that of caregiver, regardless of the health status of the dependent person (Denche-Zamorano et al, 2023). For the same reason, there is growing concern about the well-being and mental health of health professionals who earn their living by caring for users in institutions, as well as individuals who care for family members (Moriarty et al, 2015).…”
mentioning
confidence: 99%
“…As mentioned above, these two disorders can affect any person of any age, gender, ethnicity, etc. However, studies have shown that one of the roles with a higher risk of manifesting psychological problems is that of caregiver, regardless of the health status of the dependent person (Denche-Zamorano et al, 2023). For the same reason, there is growing concern about the well-being and mental health of health professionals who earn their living by caring for users in institutions, as well as individuals who care for family members (Moriarty et al, 2015).…”
mentioning
confidence: 99%